Inhibition of Virulence Gene Expression in Salmonella Dublin, Escherichia coli F5 and Clostridium perfringens Associated With Neonatal Calf Diarrhea by Factors Produced by Lactic Acid Bacteria During Fermentation of Cow Milk - Liu, Gang; Kragh, Martin Laage; Aabo, Søren; Jensen, Annette Nygaard; Olsen, John Elmerdahl (Frontiers in Microbiology, 2022)
Diarrhea is a major health problem in neonatal and young calves worldwide. It can be caused by a variety of infectious agents, including the bacteria Salmonella enterica serovar Dublin (S. Dublin), enterotoxigenic Escherichia coli (ETEC), and Clostridium perfringens. Preventive alternatives to antibiotic treatment should be identified. As a first step toward this, the aim of the current study was to examine whether cell-free supernatants from cow milk fermented by lactic acid bacteria affects virulence-gene expression in strains of S. Dublin, ETEC E. coli F5 and C. perfringens. pH-neutralized, cell-free, spent medium of milk (nCFSM) fermented by 61 different lactic acid bacteria (LAB) and non-LAB starter cultures belonging to 17 genera was assayed for their effect on expression of important virulence factors (S. Dublin hilA, ssrB, ssaG, flhD, prgI, fliC; ETEC E. coli F5 fanC, estA, fim41a; C. perfringens cpa), when the bacteria were grown in the nCFSM. Screening was done using either a promoter-reporter expression system or RT-qPCR. nCFSM from Bifidobacterium longum BL-15955 and Limosilactobacillus reuteri LR-33016 downregulated the expression of fanC, fim41a and estA genes in the four tested ETEC E. coli F5 strains without affecting their growth, while mainly B. longum BL-15955 downregulated expression of cpa in the four tested strains of C. perfringens. nCFSM from the mixed cultures; NU-TRISH® BY-Mild (Lactobacillus delbrueckii subsp. bulgaricus, Streptococcus thermophilus and Bifidobacterium BL-15954) and COMBO4 (Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus), as well as Lactobacillus helveticus CNRZ32 downregulated the tested virulence genes in the three tested strains of S. Dublin. To enable possible downregulation of the expression of virulence genes in all three target bacteria simultaneously, nCFSM was prepared from NU-TRISH® By-Mild in combination with B. longum BL-15955 (i.e. a four-strain combination). The nCFSM from this combination downregulated the virulence genes expression in all the three species. It future, NU-TRISH® By-Mild and B. longum BL-15955 in combination could potentially be used for prevention of neonatal calf diarrhea caused by S. Dublin, E. coli F5, and C. perfringens, reducing the need for antimicrobial treatment, however, field studies are needed to prove that.